FOREIGN EXPERIENCE IN REFORMING THE NATIONAL PENSION SYSTEM: AS A CASE OF THE CANADIAN PENSION SYSTEM - Shermukhamedova (International Journal of Global Economic Light, 2023)
This article delves into the definitions economists have provided for pension systems, with a specific focus on the Canadian model. We have chosen the Canadian pension system as a foundational reference for our in-depth study of global pension provisions. Our exploration encompasses the structure of Canada’s pension framework, the various programs it incorporates, and the distinct pension types under the Old Age Security (OAS) program. Additionally, we examine the unique characteristics of pension funds within this system, the demographic shifts impacting it, and forecasted changes in the income adequacy standards for Canada’s basic pensions. The study culminates with conclusions drawn from the insights gathered on this subject.